The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m114.630178
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Regulation of Smad2 Function Mediates Beclin1 Expression and Endothelial Autophagy

Abstract: Background: Endoglin is a key regulator of TGF-␤ signaling in endothelial cells but its role in autophagy during angiogenesis is unknown. Results: Endoglin relieves Smad2-dependent BECN1 repression. Conclusion: Endoglin promotes autophagy during angiogenesis by regulating Smad2 function. Significance: Endoglin-mediated autophagy may be an effective vascular target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Endothelial cells can also release exosomes containing sequestered molecules that then modulate neighbouring cells [3739]. Endothelial cells expressing high levels of endoglin also upregulate autophagy [40]. Autophagy may enhance extracellular vesicle/exosome release via the mutivesicular body pathway, especially in serum starved endothelial cells [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells can also release exosomes containing sequestered molecules that then modulate neighbouring cells [3739]. Endothelial cells expressing high levels of endoglin also upregulate autophagy [40]. Autophagy may enhance extracellular vesicle/exosome release via the mutivesicular body pathway, especially in serum starved endothelial cells [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy induces cell death, suppresses inflammation and enhances genomic stability; on the contrary, autophagy also renders cells viable in stressful conditions and is considered a pro-survival mechanism (23,24). Studies indicated that TGF-β controls autophagic responses during angiogenesis, and fibrogenesis in many human cellular systems, such as atrial myofibroblasts (25), renal tubular epithelial (26) and endothelial cells (27). Research also indicated that the TGF-β-activated fibroblasts increased autophagy and greatly sustained the growth of breast cancer cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β is an important regulator of the autophagy in a variety of cell types . As canonical effectors of TGF‐β signalling, Smad2/3 have also been shown to control autophagy . As shown in Figure D‐F, the protein levels of p‐Smad2, p‐Smad3, and TGF‐β in the TIPE2 group were lower than those in the Mock group, whereas the expression levels of these proteins in the sh‐TIPE2 group were higher than those in the sh‐Scb group.…”
Section: Resultsmentioning
confidence: 93%